Ethnoscience Knowledge of Science Teacher Candidates at UIN Mataram - Hadi Kusuma Ningrat; Desi Ratnasari; Agus Muliadi (Postgraduate, University of Mataram, 2024)
This study aims to explore the knowledge of prospective science teacher students about ethnoscience. This study is an exploratory research conducted by the Mataram State Islamic University with 17 biology education students as respondents obtained using a convenience sampling technique. The research instrument used is a closed questionnaire with answers using a Likert scale and has been validated by experts. This research data was analyzed using qualitative and quantitative descriptive statistics. The results of this research are (1) 82.35% of prospective science teacher students stated that they did not know enough about indigenous science, 70.59% stated that they did not know about ethnoscience, 70.59% stated that they did not know about the content of indigenous science in local traditions and culture, 58.82% said they didn't know enough about the relationship between indigenous science and scientific knowledge, 70.59% said they didn't know enough about the integration of indigenous science in science learning, 52.94% said they didn't know enough about ethnoscience-based learning; (2) 88.23% of prospective science teacher students showed ethnoscience knowledge in the Low category and another 11.17% showed ethnoscience knowledge in the Tall category